2016
DOI: 10.1080/00365521.2016.1203016
|View full text |Cite
|
Sign up to set email alerts
|

Presence of alcoholic steatohepatitis, but no selective histological feature, indicates an increased risk of cirrhosis and premature death

Abstract: Presence of steatohepatitis indicates an increased risk of cirrhosis and premature death. However, none of the histological parameters defining steatohepatitis can independently identify patients at risk for premature death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Of the 37 included studies, seven (including 15 204 participants) reported outcomes in AFLD, five studies (2541 participants) described outcomes in AH, 10,18,27,33,35 thirteen studies (15 302 participants) described outcomes in cirrhosis, 21–24,29,31,34,36,38,39,42,43,45 four studies (635 participants) described outcomes in decompensated cirrhosis 11–13,25 and a further 11 studies (18 866 participants) reported outcomes for ALD as a single entity 14,17,21,26,28,30,32,34,37,40,44 . Sixteen studies (6265 participants) 16,18–21,26–30,36,37,41,45–47 defined subgroups of ALD through biopsy, six studies (1642 participants) used a combination of biopsy and clinical diagnosis, 12,14,31,32,34,43 and 15 studies (42 395 participants) reported outcomes in patients diagnosed clinically 11,13,15,17,22–25,33,35,38–40,42,44 . Two further studies reported on patients with histological steatohepatitis (169 participants), but not necessarily the clinical syndrome of AH 19,41 and were considered separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 37 included studies, seven (including 15 204 participants) reported outcomes in AFLD, five studies (2541 participants) described outcomes in AH, 10,18,27,33,35 thirteen studies (15 302 participants) described outcomes in cirrhosis, 21–24,29,31,34,36,38,39,42,43,45 four studies (635 participants) described outcomes in decompensated cirrhosis 11–13,25 and a further 11 studies (18 866 participants) reported outcomes for ALD as a single entity 14,17,21,26,28,30,32,34,37,40,44 . Sixteen studies (6265 participants) 16,18–21,26–30,36,37,41,45–47 defined subgroups of ALD through biopsy, six studies (1642 participants) used a combination of biopsy and clinical diagnosis, 12,14,31,32,34,43 and 15 studies (42 395 participants) reported outcomes in patients diagnosed clinically 11,13,15,17,22–25,33,35,38–40,42,44 . Two further studies reported on patients with histological steatohepatitis (169 participants), but not necessarily the clinical syndrome of AH 19,41 and were considered separately.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 37 included studies, seven (including 15 204 participants) reported outcomes in AFLD, five studies (2541 participants) described outcomes in AH, 10,18,27,33,35 thirteen studies (15 302 participants) described outcomes in cirrhosis, [21][22][23][24]29,31,34,36,38,39,42,43,45 four studies (635 participants) described outcomes in decompensated cirrhosis [11][12][13]25 and a further 11 studies (18 866 participants) reported outcomes for ALD as a single entity. 14,17,21,26,28,30,32,34,37,40,44 Sixteen studies (6265 participants) 16,[18][19][20][21][26][27][28][29][30]36,37,41,[45][46]…”
Section: Case and Control Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three sub-types of mortality were considered: overall mortality, non-liver related mortality and liver-specific mortality. Twenty-three studies described mortality outcomes (7,9,15,17,18,22,25,33,35,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In the eight studies (including 1091 participants) that reported mortality in alcohol related steatosis (7,9,18,25,43,45,46,49), overall annual mortality was 6.0% (95%CI 4.0 -7.0%), annual non-liver mortality was 4.0% (95%CI 3.0 -6.0%) and…”
Section: Mortality In Arldmentioning
confidence: 99%